2011
DOI: 10.1007/s00441-011-1143-4
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional demonstration of the interstitial cells of Cajal associated with the submucosal plexus in guinea-pig caecum

Abstract: The guinea-pig caecum was studied by using immunohistochemistry for Kit receptors and nerves to clarify whether interstitial cells of Cajal (ICC) were localized in association with the submucosal plexus (ICC-SP). A large area of the guinea-pig caecum was nearly devoid of longitudinal muscles, because they were concentrated into three bundles of the taenia caeci (coli) and this allowed clear observation of the myenteric and submucosal plexus as separate networks in whole-mount stretch preparations. The myenteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…In contrast to the ICC-SP of the stomach (Kunisawa and Komuro 2008), ileocaecal junction (Miyamoto-Kikuta et al 2009) and caecum (Tamada and Komuro 2011), ICC-SP and their processes in the proximal colon have been frequently observed in wide connective tissue spaces away from the submucosal ganglia. Basket-like structures composed of multipolar ICC-SP have been observed around the submucosal ganglia in the caecum of the guinea pig but these structures have not been observed in the proximal colon.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In contrast to the ICC-SP of the stomach (Kunisawa and Komuro 2008), ileocaecal junction (Miyamoto-Kikuta et al 2009) and caecum (Tamada and Komuro 2011), ICC-SP and their processes in the proximal colon have been frequently observed in wide connective tissue spaces away from the submucosal ganglia. Basket-like structures composed of multipolar ICC-SP have been observed around the submucosal ganglia in the caecum of the guinea pig but these structures have not been observed in the proximal colon.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, ICC have been found in tissues that have no relationship to the tunica muscularis for gastrointestinal motility and have long puzzled researchers with regard to their functions. Such ICC lie in the subserosal layer (ICC-SS; Aranishi et al 2009) and are associated with the submucosal (submucous) plexus (ICC-SP; Kunisawa and Komuro 2008;MiyamotoKikuta et al 2009;Tamada and Komuro 2011).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…ICC are rather densely distributed in the taeniae and within the circular muscle layer. (Reproduced from Tamada and Komuro [81] with permission of the publisher). ICC-SP are found in association with the submucosal plexus.…”
mentioning
confidence: 99%
“…In adults, the ICC were identified not only within the internal anal sphincter, which is a smooth muscle, but also in a striated muscle of the external anal sphincter [Shafik et al, 2006]. Electrophysiological studies of rat, dog, and human colon have suggested that both ICC-MP and ICC-SMP are distinct pacemaker cells [Faussone-Pellegrini et al, 1990;Rae et al, 1998;Pluja et al, 2001;Alberti et al, 2007;Rumessen et al, 2009;Tamada and Komuro, 2011]. In the human gut, ICC-CM, ICC-LM, and ICC-DMP differentiate presumably in near-term fetuses, and the differentiation continues after birth [Kenny et al, 1999;Wester et al, 1999;Faussone-Pellegrini et al, 2007].…”
Section: Introductionmentioning
confidence: 99%